Enhanced antitumoral activity of doxorubicin against lung cancer cells using biodegradable poly(butylcyanoacrylate) nanoparticles - Melguizo C; Cabeza L; Prados J; Ortiz R; Caba O; Rama AR; Delgado ÁV; Arias JL (Dove Medical Press, 2015)
Consolación Melguizo1,2,* Laura Cabeza,1,* Jose Prados,1,2 Raúl Ortiz,1,3 Octavio Caba,1,3 Ana R Rama,1,3 Ángel V Delgado,4 José L Arias1,2,5 1Institute of Biopathology and Regenerative Medicine (IBIMER), Biomedical Research Center, 2Biosanitary Institute of Granada (IBS Granada), SAS Universidad de Granada, Granada, 3Department of Health Science, University of Jaén, Jaén, 4Department of Applied Physics, 5Department of Pharmacy and Pharmaceutical Technology, University of Granada, Granada, Spain *These authors contributed equally to this work Abstract: Doxorubicin (Dox) is widely used for the combined chemotherapy of solid tumors. However, the use of these drug associations in lung cancer has low antitumor efficacy. To improve its efficacious delivery and activity in lung adenocarcinoma cells, we developed a biodegradable and noncytotoxic nanoplatform based on biodegradable poly(butylcyanoacrylate) (PBCA). The reproducible formulation method was based on an anionic polymerization process of the PBCA monomer, with the antitumor drug being entrapped within the nanoparticle (NP) matrix during its formation. Improved drug-entrapment efficiencies and sustained (biphasic) drug-release properties were made possible by taking advantage of the synthesis conditions (drug, monomer, and surfactant-agent concentrations). Dox-loaded NPs significantly enhanced cellular uptake of the drug in the A549 and LL/2 lung cancer cell lines, leading to a significant improvement of the drug’s antitumoral activity. In vivo studies demonstrated that Dox-loaded NPs clearly reduced tumor volumes and increased mouse-survival rates compared to the free drug. These results demonstrated that PBCA NPs may be used to optimize the antitumor activity of Dox, thus exhibiting a potential application in chemotherapy against lung adenocarcinoma. Keywords: lung cancer, cancer chemotherapy, PBCA, polymeric nanoparticles, drug carrier